Reconstructing Self-Regulation and Self-Efficacy within Islamic Education: A Conceptual Model - Ana Safitri; Hunainah; Yahdinil Firda Nadirah; Fitri Hilmiyati (Al-Mudarris, 2026)
This study addresses the lack of an integrative model that reconstructs self-regulation and self-efficacy within an Islamic epistemological framework in Islamic Religious Education (IRE). Previous studies have predominantly examined these constructs from Western psychological perspectives, with limited attention to their conceptual alignment with Islamic values and their operational integration in learning. Therefore, this study aims to develop an analytical conceptualization of self-regulation and self-efficacy grounded in Islamic principles and to explain their relationship with students’ learning outcomes in IRE. This study adopts a qualitative method through a library research approach. The data sources consist of academic books, reputable journal publications, and previous studies relevant to the topic, and analyzed through content analysis, including data reduction, categorization, and interpretative synthesis. The findings indicate that self-regulation, when reconstructed within an Islamic framework, encompasses dimensions such as niyyah (goal intention), muraqabah (self-monitoring), muhasabah (self-evaluation), and sabr (self-control). Meanwhile, self-efficacy is conceptually aligned with tawakkul (trust in Allah), yaqin (conviction), and husn al-zann (positive belief), which strengthen students’ confidence and resilience in learning. Operationally, self-regulation functions as a strategic process (planning, monitoring, evaluation), while self-efficacy acts as a motivational foundation influencing persistence and engagement. The integration of these constructs forms a coherent learning mechanism that enhances students’ cognitive, affective, and psychomotor outcomes in IRE. This study contributes by proposing an Islamic self-regulated learning framework that integrates spiritual values with psychological constructs, offering both conceptual reconstruction and operational dimensions for developing holistic and contextually relevant Islamic education.